Reading and Literacy Intervention at Building Hope Community School - Wright, Sarah E (My University, 2025)
Over the course of 5 semesters, students received reading and literacy intervention that we failing below grade level performance at Building Hope. Each student was given individual tutoring sessions that met their specific needs, as well as given reading and literacy activities to engage and empower the student both inside and outside the classroom. This initiative later developed into Academy of Scholars, which is an official program and Building Hope that is dedicated towards increasing student literacy performance in individuals performing below grade level standard.
Keywords: Reading intervention; tutoring; child literacy